A Hyperactive NAD(P)H:Rubredoxin Oxidoreductase from the Hyperthermophilic Archaeon Pyrococcus furiosus - Ma, Kesen (American Society for Microbiology, 1999)
NAD(P)H:rubredoxin oxidoreductase (NROR) has been purified from the hyperthermophilic archaeon Pyrococcus furiosus. The enzyme is exceedingly active in catalyzing the NADPH-dependent reduction of rubredoxin, a small (5.3-kDa) iron-containing redox protein that had previously been purified from this organism. The apparent V(max) at 80°C is 20,000 μmol/min/mg, which corresponds to a k(cat)/K(m) value of 300,000 mM(−1) s(−1). The apparent K(m) values measured at 80°C and pH 8.0 for rubredoxin, NADPH, and NADH were 50, 5, and 34 μM, respectively. The enzyme did not reduce P. furiosus ferredoxin. NROR is a monomer with a molecular mass of 45 kDa and contains one flavin adenine dinucleotide molecule per mole but lacks metals and inorganic sulfide. The possible physiological role of this hyperactive enzyme is discussed.